Supporting and Scaling Up Youth Agripreneurship in Kenya - Dianga, Alex Wasonga; Lohento, Ken; Bosire, Eric (Technical Centre for Agricultural and Rural Cooperation, 2020)
This analytical document on rural youth agribusiness is a source of evidence-based knowledge for youth in agriculture, or those doing agribusiness as well as organisations or entities implementing or supporting youth agribusiness in Kenya. The 9 articles in this document cover themes such as access to finance, business mentorship, ICTs and social media for agribusiness, market linkages and access that effectively shape-up and enhance rural youth agribusiness in Kenya and beyond. The articles were submitted by authors who responded to a call for articles launched by the project.